"On" or "for" Nothing/Rien: Nothing, Silence and Noise in Samuel Beckett and John Cage. Issue 3 (2nd July 2020) - Smith, Jackson B.
Abstract: This is a comparative study of Samuel Beckett's Textes pour rien (1950, published 1958) and John Cage's Lecture on Nothing (1949, published 1961). These two projects, each of which emblematizes the lifelong artistic pursuit of its creator, offer a glimpse at the affinity between the two creators themselves. This article examines these two works and their authors according to three axes: first, nothing and how it is defined and deployed in each author's creation, with an emphasis on the function of the prepositions "on" and "for" used in each author's title; second, silence, which, in both cases, serves an important function as one of nothing's major phenomenological counterparts—notably in Cage's subsequent composition 4'33" and in Beckett's quest to suppress the narrative voice of subjectivity; third, noise, which I will claim is the paradoxical but determinant residue that results from each author's search for nothing and for silence.